Characteristics and evaluation of the effectiveness of monitoring and control measures for the first 69 Patients with COVID-19 from 18 January 2020 to 2 March in Wuxi, China. (January 2021) - Shi, Ping; Gao, Yumeng; Shen, Yuan; Chen, Enping; Chen, Hai; Liu, Juan; Chen, Yujun; Xiao, Yong; Wang, KeWei; Shi, Chao; Lu, Bing
Highlights: The dynamic parameters proved that our early control measures were effective. The incubation period calculated using a single exposure of 9 patients was 8.59 days. We found that high age and fever were risk factors for disease severity. Early detection of asymptomatic carriers was important to control transmission. Abstract: Background: The Coronavirus disease (COVID-19) has caused 91, 305 confirmed cases and 4746 deaths in China by 13:50 on October 11, 2020. We analyzed data on 69 infections in Wuxi to describe the disease's characteristics, to analyze factors of cases clinical outcome and to evaluate the prevention and control measures. Methods: The demographic characteristics, exposure history, time indicators and propagation dynamics in Wuxi were collected. Results: The clinical severity of cases was mostly mild and normal (75.36 %). Aging (relative risk [RR] = 1.04, 95 % confidence interval [CI]: 1.001–1.08) and fever (RR = 10.33, 95 %CI: 2.75–38.78) were risk factors for disease severity. The mean incubation period was estimated to be 4.77 days (95 % CI: 3.61–5.94), with a mean serial interval of 6.31 days (95 % CI: 5.12–7.50). The controlled reproduction number was estimated to be 1.12 (95 %CI: 0.71–1.69). Conclusions: The incidence of COVID-19 in Wuxi has turned into a lower level, suggesting the early prevention and control measures have achieved effectiveness. Aging and fever of initial symptom were risk factors for severe clinical outcome. The family clusters provided further clues of the risk factors for COVID-19 transmission.